Promoting pharmaceutical care services: a case report. Issue 4 (20th June 2012) - Curatolo, Niccolo; Desnoyer, Aude; Chaumais, Marie-Camille; Courtin, Claire; di Giuro, Giuseppe; Rieutord, André
Abstract : To illustrate the potential benefits of ward-based clinical pharmacy, the case is reported of a patient who benefited from three successful pharmaceutical interventions. The patient visited the emergency department with an epigastric pain and a vitamin K antagonist overdose was suspected. Prothrombin complex concentrates were prescribed by the emergency physician. Analysis of the patient's parameters did not show evidence of any sign of major bleeding so the order was cancelled after the intervention of the on-call pharmacy resident. Medication reconciliation performed by another resident showed two major unintended discrepancies: vigabatrin prescription had been omitted and sotalol was prescribed at the wrong dose. The physician was informed and the prescription order corrected. Eventually the pharmacy resident responsible for anticoagulant therapy education visited the patient. Careful investigation of the patient's medical chart led him to suggest discontinuation of the anticoagulant therapy. This intervention resulted in the immediate discharge of the patient. This case report highlights the added value of pharmaceutical care performed on the ward and illustrates both the clinical benefit for the patient and the economic benefit for the hospital. This topic is rarely discussed in case reports. This paper demonstrates its value and argues to extend its practice.